The acasta conundrum: Polymorphism and taxonomic confusion within the parasitoid genus Melittobia (Hymenoptera: Eulophidae) - Matthews, Robert W.; González, Jorge M. (Zootaxa, 2008)
Seven of the 13 described species of this gregarious, polyphagous, polymorphic parasitoid have been placed in the acasta species group of Melittobia Westwood (Hymenoptera: Eulophidae: Tetrastichinae) based on ethological and morphological criteria, but taxonomic confusion remains. Based on field and laboratory studies of variability and polymorphism, current species descriptors for this group are called into question and Melittobia femorata Dahms is synonymized under M. megachilis (Packard). Biologically, M. megachilis distinctly differs from other acasta group species in several aspects of life cycle and host utilization. Although M. acasta (Walker) and M. digitata Dahms are clearly valid species, three others (M. chalybii Ashmead, M. scapata Dahms, M. evansi Dahms) are more enigmatic and may be temporal, nutritional, or host-based variants of M. megachilis that will require additional study. The “Virginia” type locality for M. chalybii of authors is properly Bladensburg, Maryland, USA. One of the 13 female syntypes of Chrysocharis aeneus Brues (previously synonymized under M. megachilis) is designated as Lectotype.